2022
DOI: 10.31234/osf.io/qa8ys
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Facilitation and interference are asymmetric in holistic face processing

Abstract: A hallmark of face specificity is holistic processing. It is typically measured by various paradigms such as the part-whole and composite tasks. However, these tasks do not seem to test the same construct, so a comprehensive account of holistic processing remains elusive. Here we investigated the nature of facilitation and interference observed in congruent and incongruent trials in the complete composite face task. These two aspects are asymmetrically influenced by the location and cueing probabilities of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Consistent with recent findings that facilitation and interference in holistic face processing may operate somewhat independently (Jin, Ji, et al, 2022), our results suggest that the separate contributions from facilitation or interference in PW, SC, and CC might have resulted in the mixed findings in the literature. Because both facilitation and interference that contribute to the holistic effect can be measured by the congruency effect in CC, we suggest that CC may be a more complete measure of holistic processing than the other tasks if both components of holistic processing are of interest.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with recent findings that facilitation and interference in holistic face processing may operate somewhat independently (Jin, Ji, et al, 2022), our results suggest that the separate contributions from facilitation or interference in PW, SC, and CC might have resulted in the mixed findings in the literature. Because both facilitation and interference that contribute to the holistic effect can be measured by the congruency effect in CC, we suggest that CC may be a more complete measure of holistic processing than the other tasks if both components of holistic processing are of interest.…”
Section: Discussionsupporting
confidence: 90%
“…We proposed that these tasks might measure two aspects of holistic face processing-facilitation and interference (Jin, Ji, et al, 2022). As facilitation and interference can be quantified in CC by comparing performance in congruent or incongruent trials with the isolated trials (e.g., Richler et al, 2008), we suggest that the whole face context in PW provides congruent information to aid identification of the target facial feature, whereas the different bottom halves in SC produces incongruent information to impair the matching of the identical top halves.…”
mentioning
confidence: 99%
“…There are several different composite-face paradigms 55 57 . The standard design (or original design, partial design) and the complete design are the most widely used paradigms 55 58 . There has been an intensive debate between both paradigms 59 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers suggested that in the standard paradigm, the congruency and response type are confounded, and the alignment effects may arise from differential response biases. A preprinted study by Jin et al offered an alternative explanation of difference between standard design and complete design 55 . The researchers found that there are two aspects of the influence of irrelevant facial parts on the target parts in the complete composite paradigm: facilitation in congruent trials and interference in incongruent trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation